Asparagus racemosus improves seminal antioxidant status and sperm characteristics in buck semen at refrigeration temperature - GANGWAR, CHETNA; KUMAR, ASHOK; MISHRA, ANIL KUMAR; KHARCHE, S D; SWAROOP, KAMENDRA; POUROUCHOTTMANE, R; GOEL, RAKESH; SINGH, SHRIPRAKASH (The Indian Journal of Animal Sciences, 2023)
The present investigation was carried out to evaluate the effect of Asparagus racemosus (Shatavari) aqueous extract on buck semen quality during preservation. In the current study, 8 ejaculates from 8 Jakhrana bucks maintained at Jakhrana unit of ICAR-CIRG (semi-arid region) were collected (total 64 ejaculates) during the period from April to June, 2022. Good quality semen samples were pooled during each collection. Pooled semen samples were then divided into 4 equal parts, and diluted in TRIS buffer containing different concentration of Shatavari aqueous extract (Different groups, i.e. Gr1-5 mg, Gr2-2.5 mg, Gr3-1.25 mg, Gr4-0 mg of Shatavari aqueous extract/ml of semen diluent). All the diluted semen samples were kept at refrigerated temperature (5°C) for seven days, and on each day, diluted semen was evaluated for various sperm characteristics and antioxidant status. Gr3 showed significantly better results in terms of sperm viability, sperm motility, acrosomal integrity and plasma membrane integrity. Along with this, the longevity of sperm was also enhanced in Shatavari supplemented group.